2003
DOI: 10.1007/s00011-003-1191-7
|View full text |Cite
|
Sign up to set email alerts
|

Histaminergic receptors modulate the coronary vascular response in isolated guinea pig hearts. Role of nitric oxide

Abstract: These results suggest that, in isolated guinea pig hearts, histamine produces coronary dilation through an H (2 )/H (3 )-dependent mechanism involving the generation of nitric oxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
5
0
2
Order By: Relevance
“…However, rat hearts do not possess functional H 2 -histamine receptors. After a myocardial infarction, histamine is released, at least in part, from mast cells in the myocardium ( Pierpaoli et al, 2003 ). Indeed, the extent of the increase in histamine in the plasma in dogs after coronary occlusion was correlated with the severity of the arrhythmias, which Wolff and Levi (1988) showed in their review.…”
Section: Roles Of Histamine and Histamine Receptors In Cardiac Diseasementioning
confidence: 99%
“…However, rat hearts do not possess functional H 2 -histamine receptors. After a myocardial infarction, histamine is released, at least in part, from mast cells in the myocardium ( Pierpaoli et al, 2003 ). Indeed, the extent of the increase in histamine in the plasma in dogs after coronary occlusion was correlated with the severity of the arrhythmias, which Wolff and Levi (1988) showed in their review.…”
Section: Roles Of Histamine and Histamine Receptors In Cardiac Diseasementioning
confidence: 99%
“…It emerges clearly that, in addition to the respiratory tract, the cardiovascular system is a major target of anaphylactic reaction, due to the striking vascular and cardiac effects of mediators derived from activation of tissue mast cell and circulating basophils, such as histamine (in the short term) and arachidonic acid metabolites and chemokines (in the longer term). Detailed analysis of the well-known actions of these mediators on peripheral blood vessels-chiefly vasodilatation and increased endothelial permeability [5]-is beyond the scope of this article, which is rather focused on the cardiac effects of IgE-mediated allergic disease and its regulation by histamine and gaseous autacoids, such as nitric oxide (NO) and carbon monoxide (CO).…”
Section: Introductionmentioning
confidence: 99%
“…Although this eNOS upregulation may be protective under normal circumstances, as it increases NO production, it may become harmful under conditions of oxidative stress when eNOS produces reactive oxygen species (ROS) at the expense of NO [1518]. Also, it is shown that histamine produces coronary dilation via H2 receptor, which is not endothelium dependent [11, 12], as well as through H2- and H3-dependent mechanism involving the generation of nitric oxide [19]. …”
Section: Introductionmentioning
confidence: 99%